Preparation of Ti/TiO2 anode for electrochemical oxidation of toxic priority pollutants - Yaqub, A. (Ecole Polytechnique de Montreal, 2017)
In present study, Ti/TiO2 anodes were prepared in laboratory for degradation of polycyclic aromatic hydrocarbons. Polycyclic aromatic hydrocarbons considered as priority pollutants because of their carcinogenetic properties. PAHs were electrochemically oxidized under galvanostatic conditions using TiO2 coated Ti anode. A synthetic solution containing 16 priority PAHs were prepared in the lab. Surface morphology showed cracked mud structure of coated Ti/TiO2 surface. All the PAHs were efficiently oxidized and degraded from solution. About 96.87 of σPAHs were removed in five hours from the bulk solution. The results showed the potential of electrochemical process with Ti/TiO2 anode as a possible and reliable technique for the degradation of PAHs in water. © 2017 J. New Mat. Electrochem. Systems.